A case report: Is mexiletine usage effective in the shortening of QTC interval and improving the T‐wave alternans in Timothy syndrome?. Issue 3 (30th November 2017) - Tunca Sahin, Gulhan; Ergul, Yakup
Abstract : Timothy syndrome (TS) is a multisystemic disease that occurs because of a mutation in CACN1C gene and is characterized by prolonged QT interval. Mexiletine is a Class 1B antiarrhythmic drug that causes the disappearance of T‐wave alternans by shortening QTc and peak‐to‐end of the T wave. It may block the development of torsades de pointes in a prolonged QT. This study presented the case of a patient diagnosed with TS and had a cardiac arrest history, prolonged QT, and T‐wave alternans. After mexiletine treatment, the QTc interval shortened and T‐wave alternans disappeared. Such a case has rarely been seen in the literature, and hence considered rare. This case presentation was of particular importance because it highlighted the use of mexiletine besides an initial beta‐blocker treatment in the cases with TS.